(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
The purpose of this study is to determine the appropriate method for micaceous iron ore processing and production per-industrial application standards. After identifying the characteristics of the samples (with XRF, XRD, mineralogical analyzes), gravity and magnetic separation tests were carried out. Quartz and hematite are the main minerals of micaceous hematite ores. Silica grade as the major impurity varies from 10-68 %. The total iron content of the samples also varies from 15-62 %. Jig and shaking table did not provide a good result in micaceous hematite beneficiation to achieve the standard of its specific applications. Gravity concentration by the spiral in the size range of -200 and -300 µm has led to the production of iron concentrates with a grade of 62.34 and 64.84 %, respectively. The recovery values for the two experiments are 13.50 and 12.60 %, respectively. Therefore, the spiral did not provide a good result in the micaceous iron ore beneficiation. High-intensity magnetic separation (1.2 T) has resulted in a product with a grade and recovery of 65.98 % and 88.35 %, respectively. The experimental design utilizing the Taguchi method considering the increasing of grade or recovery priority indicated that for micaceous iron beneficiation with a priority of recovery increasing, the feeder frequency, roll speed, and adjustable gate angle should be at 6.5 Hz, 95 rpm, and 20°, respectively. However, for micaceous iron beneficiation with a priority of grade increasing, the feeder frequency, roll speed, and adjustable gate angle should be at 2.5 Hz, 135 rpm, and 60°, respectively.